Burden of colorectal cancer attributable to dietary risks in China from 1990 to 2021: findings from the Global Burden of Disease Study 2021 - Chen, Bijuan; Zheng, Hanchen; Huang, Rui; Yu, Jiami; Wang, Xiaojie; Yang, Chunkang; Guo, Zengqing; Zhan, Zhouwei (Frontiers in Nutrition, 2026)
BackgroundColon and rectum cancer (CRC) poses a major public health challenge in China, with dietary risks identified as key modifiable contributors to its incidence and mortality. Quantifying the current burden, long-term trends, and the impact of specific dietary factors is essential to inform effective prevention strategies.MethodsData on CRC burden attributable to dietary risks in China from 1990 to 2021 were extracted from the Global Burden of Disease Study 2021. We examined all-age numbers and age-standardized rates of CRC deaths, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). Temporal trends and generational patterns were explored using joinpoint regression, age-period-cohort, and decomposition analyses.ResultsIn 2021, dietary risks accounted for over 102,000 CRC-related deaths and 2.55 million DALYs in China, with a significantly higher burden among males. Although age-standardized mortality, DALY, and YLL rates declined modestly over the past three decades, YLD rates increased. Diets low in milk, whole grains, and calcium were the predominant contributors, while the burden associated with processed meat showed the largest relative increase. The highest burden occurred among those aged 65–74, with notable sex disparities. Joinpoint analysis revealed fluctuating trends, including recent plateaus or increases, particularly in males. Age-period-cohort analysis indicated elevated burden in earlier birth cohorts, with improvements in more recent generations. Decomposition analysis identified population aging as the primary driver of burden growth, whereas epidemiological changes contributed modest reductions, especially among women.ConclusionThe burden of CRC attributable to dietary risks remains considerable in China, underscoring the need for targeted, gender- and age-sensitive dietary interventions to reduce premature mortality and long-term disability.